Femtocell interference mitigation - Zyoud, Al-Hareth; Habaebi, Mohamed Hadi; Chebil, Jalel; Islam, Md. Rafiqul (IEEE, 2012)
The demand for the Femtocells deployment is in the rise since it enhances the wireless link and increase the capacity for the wireless network. Femtocell is a home base station designed for use in residential and business areas such as houses, apartments, offices, schools, and markets. It connects to the service provider’s network via broadband and normally supports 2 to 6 mobile phones in a small area. Using femtocell will enhance the indoor coverage, save power since it reduces the transmitted power, and in the same time reduce the traffic on microcell. However, the most important challenge in femtocell deployment is interference mitigation and management. In this paper, a state of the art literature review on mitigating interference is presented. First, interference in femtocell environment is classified from different point of views. Then, open issues for femtocell interference research are discussed.